Penguatan Sentra Kewirausahaan Pemuda Gampong Pante Rawa Aceh Besar Melalui Program Inkubator Bisnis Kemenpora - Akmal Saputra; Cut Irna Liyana (Universitas Teuku Umar, 2020)
This article examines how the business incubator program by the Ministry of Youth and Sports (Kemenpora) through the Aceh Ummat Development Institute (LPU) in 2013 has influenced and given impact the Youth Entrepreneurship Center (SKP) in the Pante Rawa village, Kecamatan Kuta Malacca, Aceh Besar Regency. This study uses qualitative methods with purposive techniques, data collection techniques through in-depth interviews, documentation of activities and observation after the program is implemented. The results showed that the Business Incubator program implemented by the Ministry of Youth and Sport had an impact on the independence of youths in the villages, the formation of Youth Entrepreneurship Centers (SKP), encouraging entrepreneurship, impacting on creative, innovative values and youth participation in entrepreneurship, the realization of youth values togetherness at Pante Rawa village, Kuta Malaka sub-district, Aceh Besar District